P-P21 Endoscopic bipolar radiofrequency ablation for treating biliary obstruction caused by unresectable cancer: systematic review of clinical and cost effectiveness. (16th December 2021) - Beyer, Fiona; Rice, Stephen; Orozco-Leal, Giovany; Still, Madeleine; O'Keefe, Hannah; O'Connor, Nicole; Stoniute, Akvile; Craig, Dawn; Pereira, Stephen; Carr, Louise; Leeds, John
Abstract: Background: Early evidence suggests using radiofrequency ablation (RFA) as an adjunct to stenting may improve outcomes in patients with malignant biliary obstruction. RFA can be deployed either at the initial stent insertion or to clear tumour ingrowth in a previously placed stent. Methods: To assess the clinical and cost effectiveness and potential risks of RFA for malignant biliary obstruction. MEDLINE, EMBASE, Cochrane Library, Scopus, CINAHL, HTA and DARE, 3 websites and 7 trial registers were searched from 2008 to 2021. Study inclusion criteria were: malignant biliary obstruction; intervention as endoscopic RFA, either to fit a stent (primary RFA) or to clear a blocked stent (secondary RFA); primary outcomes were survival, quality of life or procedure-related adverse events. Risk of bias was assessed using the RoB 2.0 and ROBINS-I tools. Primary analysis was meta-analysis of the hazard ratio of mortality. Results: 68 studies (1742 patients) were identified but only 2 randomised trials, 1 retrospective case-control study and 3 retrospective cohort studies reported a hazard ratio of death for primary RFA compared to stent-only control. The pooled hazard ratio of mortality for primary RFA compared to stent-only was 0.34 (95% confidence interval (CI) 0.21 to 0.55). There was moderate heterogeneity (I 2 = 53%) however studies were consistently in favour of primary RFA. There was insufficient evidence available to analyse effectiveness in secondary RFA. No evidence relating to quality of life. There was no evidence of increased risk of cholangitis (risk ratio 1.15, 95% CI 0.63 to 2.12) or pancreatitis (risk ratio 1.34, 95% CI 0.55 to 3.25), but there was an increase in cholecystitis (risk ratio 11.47, 95% CI 2.28 to 57.66). Inconsistencies in standard reporting and study design were noted e.g. adverse outcomes and lack of standardised comparator groups. RFA was estimated to cost £2, 659 and produced 0.18 QALYs more than no RFA on average. With an ICER of £14, 392/QALY, RFA was likely to be cost-effective at a threshold of £20, 000/QALY. The source of the vast majority of decision uncertainty lay in the effect of RFA on stent patency. Conclusions: Primary RFA is associated with increased survival and appears cost-effective. The evidence for the impact of secondary RFA on survival and of quality of life is limited. There was no increase in the risk of post-ERCP cholangitis or pancreatitis but increased risk of cholecystitis. High quality RCTs to investigate primary and secondary RFA are needed with accurate documentation of quality of life, adverse event rates and survival.